Actualization Of Ibnu Rusyd's Multiculturalism Thinking (Study of the Bidāyah al-Mujtahid Book at the Hidāyah al Mubtadi'in Lirboyo Islamic Boarding School and the Rafah Bogor Modern Islamic Boarding School) - Mumtazah, Afwah; Djubaidi, Dedi; Sahrodi, Jamali (International Journal of Education and Digital Learning (IJEDL), 2024)
The 2019 political contest brought its own records to the Indonesian nation. Political polarization develops into religious polarization. This polarization is then manifested in identity politics which is enlivened by mutual arguments, mutual criticism, and mutual insults. The aim of this research is to discover and explain the growth of Ibn Rushd's multiculturalist thinking, and to analyze multicultural studies in the book Bidāyah al-Mujtahid. This research uses a qualitative and field (empirical) approach. The biographical method is used to obtain data about the uniqueness of Ibn Rushd's multicultural educational thoughts in Bidāyah al-Mujtahid. The results of this research found firstly, the growth of Ibnu Rushd's multiculturalist thinking was due to internal and external factors. He grew up in an educated family, with a profession as a respected and religious judge. The family freed Ibnu Rushd's education as desired. Externally he obtained various achievements and scientific support as well as positions, such as judge, ambassador, doctor, and advisor to the caliph. This conducive environment allowed Ibnu Rushd's multicultural thinking to grow. Second, in the legal istinbāṭ carried out by Ibn Rushd in the book Bidāyah al-Mujtahid always involves the reality of context, culture, political customs, maqaṣid syarī'ah and its epistemology, so that the resulting legal decisions appear multicultural. Third, the actualization and implementation of Ibnu Rushd's multiculturalism values by establishing Bidāyah al-Mujtahid as a curriculum and creating a national jurisprudence book to equip students to behave tolerantly. viii Extracurricular activities in both Islamic boarding schools that carry the spirit of Ibnu Rushd's multiculturalist thoughts are found in Lajnah Bahts al-Masāil (LBM) and Fatḥu al-Kutub al-Usbū'iyah.